Databases in University of Malaya Library System: part I: circulation control, bibliographic and management activities. - Lee, A. (University of Malaya Library, 1990)
The two part article will illustrate an important contribution of microcomputers to the computerisation programme of University of Malaya Library (UML). It gives an overview of computerised databases available in the University of Malaya Library system. A general overview of UML's computerisation programme is discussed to provide a background to UML's approach to its computerization programme and the acquisition of the present computer systems. A survey was conducted to identify various computerised databases available and where appropriate samples of reports are provided. The results show that many databases are in existence and most of these fulfill a practice a functional purposes. Though most of the databases are for in-house use, there are plans to incorporate them into the forthcoming intergrated computerised library system.